Evolving approaches to the study of childhood poverty and education. Issue 1 (2nd January 2017) - Hannum, Emily; Liu, Ran; Alvarado-Urbina, Andrea
ABSTRACT: Social scientists have conceptualised poverty in multiple ways, with measurement approaches that seek to identify absolute, relative, subjective, and multi-dimensional poverty. The concept of poverty is central in the comparative education field, but has been empirically elusive in many large, international educational surveys: these studies have not typically included measures that correspond to prevalent conceptualisations or measurement strategies in the poverty literature. In this paper, we contrast poverty conceptualisation and measurement in the poverty literature with socio-economic measures prominent in major international educational surveys. Disconnects between these approaches, and implications for understanding how the disadvantages of poverty in childhood are reflected in educational surveys, are considered. We discuss key challenges that continue to shape possibilities for incorporation of poverty-related concepts into educational surveys. We close with a set of recommendations and considerations.